Investigational Model to Generate Aggregate Value in Eco-sustainable Housing Development - Montagner, Ernesto Adrian Diaz; Garcia, Juan Carlos Perez (European Scientific Journal, ESJ, 2018)
Purpose – Conventional materials and procedures in worldwide construction sector is a paradigm that requires change. Constructors usually do not take the adventure of testing novel techniques and materials in their construction projects and, as a result, profits are usually given in terms of time and cost savings. The purpose of this article is to introduce a model to add aggregate value in eco-sustainable dwelling construction through ecological sustainable value chain and hypothesis settlement. Design/methodology/approach - A review of the literature was done in databases using keywords. The selection of sources includes scientific articles and case studies based on different methods and contexts which were carried out. Findings - The findings suggest the implementation of the training of both the employee who works in the construction and the client regarding selfsustainable construction. A significant improvement was obtained based on the commercial relations of suppliers, the client, and also with the construction company. Finally, innovation in at least one of the six proposed aspects was carried out: new technologies, including eco-technologies, the quality of materials (including the eco-sustainable ones), the segmentation of the demand for eco-sustainable housing and its new ways of marketing and financing. They were, however, proposed for added value generation for the development of eco-sustainable housing. Originality/value - A model for the generation of added value in the construction of eco-sustainable housing was elaborated based on the relationships between human and relational capital, training, and the generation of aggregate value.